2016
DOI: 10.14814/phy2.13031
|View full text |Cite
|
Sign up to set email alerts
|

Breathing 100% oxygen during water immersion improves postimmersion cardiovascular responses to orthostatic stress

Abstract: Physiological compensation to postural stress is weakened after long‐duration water immersion (WI), thus predisposing individuals to orthostatic intolerance. This study was conducted to compare hemodynamic responses to postural stress following exposure to WI alone (Air WI), hyperbaric oxygen alone in a hyperbaric chamber (O2 HC), and WI combined with hyperbaric oxygen (O2 WI), all at a depth of 1.35 ATA, and to determine whether hyperbaric oxygen is protective of orthostatic tolerance. Thirty‐two healthy men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Previous work from our laboratory demonstrated that a 6-h water immersion while breathing air increased sympathetic nervous system activity, specifically leading to peripheral vascular resistance and a decrease in peripheral blood flow (i.e., forearm and calf muscles) (9). Interestingly, breathing 100% O 2 during the same conditions attenuated the decrease in peripheral blood flow compared with breathing air (32). It is possible that oxygen consumption during exercise after repeated long-duration diving with air was decreased as a result of decreased peripheral blood flow to the working muscles and, more generally, autonomic alterations after water immersions breathing air.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work from our laboratory demonstrated that a 6-h water immersion while breathing air increased sympathetic nervous system activity, specifically leading to peripheral vascular resistance and a decrease in peripheral blood flow (i.e., forearm and calf muscles) (9). Interestingly, breathing 100% O 2 during the same conditions attenuated the decrease in peripheral blood flow compared with breathing air (32). It is possible that oxygen consumption during exercise after repeated long-duration diving with air was decreased as a result of decreased peripheral blood flow to the working muscles and, more generally, autonomic alterations after water immersions breathing air.…”
Section: Discussionmentioning
confidence: 99%
“…It seems reasonable to assume that a small translocated volume can generate local interstitial edema sufficient to irritate nerves without affecting overall pulmonary function parameters. However, the hypovolemia that follows from immersion [ 15 , 16 , 17 ] may have moderated the increased filtration pressures in the lungs in the wet divers despite the sustained increase in central venous pressure [ 18 ]. Hypovolemia was likely cumulative across the dive week [ 15 ], and perhaps more severe than that during the previous series of six-hour wet resting oxygen dives [ 2 ] when divers were less restricted.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was conducted as part of a larger research project examining the neurophysiological response to repeated diving under a variety of conditions. 7,26 Participants completed a 6-hour dive once daily for 5 days with outcome measures collected before and after each dive. The analyses presented in this manuscript were limited to data collected during the first day (ie, immediately before and after the first dive exposure) so as to avoid effects related to training, learning, or chronic adaptation.…”
Section: Subjectsmentioning
confidence: 99%